Growth of Bacteria Bacillus cereus in Liquid Media with Different Protein Sources - Mukti, Pranata Rangga; Feliatra, Feli; Effendi, Irwan (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2020)
The aim of this research was to determine the optimal media composition and incubation time for the growth of Bacillus cereus and B. cereus isolate consortium with other strains isolate. Using an experimental method, which was testing 2 groups of bacterial isolates; B. cereus strain SN7 (isolate N) and bacterial consortium (combination of 5 isolates of B. cereus with different strains). Each group of isolates was grown in sago waste media added with two different protein sources (egg whites and skim milk) and 3 different concentrations in each protein source (8%, 10%, and 12%) with 3 replications in each treatment. Bacterial culture was measured every 6 hours for 24 hours using three methods; total agar plate count, spectrophotometric methods, and bacterial cell biomass methods. There was no significant difference between the growth of these two groups of bacterial isolates. Optimal growth of each isolate was in the sago waste media which was added with egg white but with different concentrations, namely 10% in B. cereus SN7 and 12% in the consortium. B. cereus consortium showed higher growth than B. cereus SN7. The optimal time for bacteria to grow was in the range of 12 to 24 hours